Hyperoxia shows duration-dependent effects on the lengths of cell cycle phases in fetal cortical neural stem cells - Lanto, Jennifer; Vehlken, Monika Maria Nicole; Abramenko, Valeriia; Storch, Alexander; Markert, Franz (Frontiers in Cell and Developmental Biology, 2025)
Fetal neural stem cells (NSCs) physiologically reside under low-oxygen conditions (1%–5% of tissue pO2), but are often transferred and maintained under atmospheric oxygen levels of 21% pO2 (hyperoxia) for in vitro investigations. These altered oxygen conditions lead to adaptive changes in NSCs which complicate the interpretation of in vitro data. However, the underlying adaption dynamics remain largely enigmatic. Here we investigated short-term hyperoxia effects (5 days in 3% pO2 followed by 2 days in 21% pO2) in comparison to continuous hyperoxia effects (7 days in 21% pO2) and physioxic control (7 days in 3% pO2). We utilized cortical NSCs to analyze the cell cycle phases by flow cytometry and cumulative BrdU incorporation assay. NSCs showed a severe reduction of cell proliferation when cultivated under continuous hyperoxia, but no changes after short-term hyperoxia. Subsequent cell cycle analysis as assessed by flow cytometry revealed a clear shift of NSCs from G0/G1-phase towards S- or G2/M-phase after both continuous and short-term hyperoxia. However, while cell cycle length was dramatically reduced by short-term hyperoxia, it was increased during continuous hyperoxia. Taken together, our results demonstrate the beneficial effect of physioxia for expanding NSCs in vitro and reveal differential effects of short-term hyperoxia compared to continuous hyperoxia.